Hambatan belajar siswa pada materi kaidah pencacahan - Santosa, Farah Heniati; Indrawati, Indrawati; Bahri, Samsul (Jurnal of Math Tadris, 2024)
This article aims to identify students' learning obstacles in learning mathematics, especially in the material of enumeration rules. This study uses a descriptive exploratory design. Data were collected through tests, in-depth interviews with students and teachers, and classroom observation techniques. The results show that students face epistemological, ontogenic, and didactic learning obstacles. Epistemological obstacles are seen from students' difficulties in distinguishing between the concepts of permutation and combination. Ontogenic obstacles include weaknesses in mastering prerequisite materials, such as basic mathematical operations, and low student self-confidence. Didactic obstacles arise from less varied learning methods, with the dominance of lecture methods and minimal use of visual aids or interactive media. The main factors causing obstacles involve a combination of internal factors, such as limited understanding of concepts and operational errors of students, and external factors, such as teaching strategies that are less adaptive to students' needs. Based on these findings, recommended learning strategies include the use of visual aids, problem-based learning approaches, group-based learning, and reinforcement of prerequisite materials through gradual exercises.